Scanning probe microscopy installed with nanotube probes and nanotube tweezers - Nakayama, Yoshikazu (Ultramicroscopy, 2002)
We have developed well-controlled processes for the growth and manipulation of carbon nanotubes. The relatively thin multiwalled nanotubes were prepared with high purity by arc discharge with a high gas temperature. In the manipulation of nanotubes, the first crucial process is to prepare a nanotube array, so-called nanotube cartridge. We have found the alternated current electrophoresis of nanotubes by which nanotubes are aligned at the knife-edge of a disposal razor. The second important process is to transfer a nanotube from the nanotube cartridge onto a substrate in a scanning electron microscope. Using this method, we have developed nanotube probes and nanotube tweezers that operate in a scanning probe microscope (SPM). The nanotube probes have been applied for observation of biological samples and industrial samples to clarify their advantages. The nanotube tweezers have been demonstrated for their motion in scanning electron microscope and operated to carry a nanomaterial in a SPM.